Suppression of Nearest Neighbour Electron Hopping in FeSe-Based Superconductors - Pustovit, Yu.V.; Kordyuk, O.A. (Металлофизика и новейшие технологии, 2018)
In this paper, we evaluate the fitting parameters for the hopping model for the dxy and dxz bands within the Γ–M cut for different FeSe-based superconductors. Comparison of these parameters for DFT calculations and for experimentally obtained data reveals a dramatic change of hopping probability between the nearest neighbours. This change is much bigger than the expected band renormalization and can be explained by the appearance of an antiferromagnetic-like ordering.